2013
DOI: 10.1590/s1516-14392013005000165
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of minimum quantity lubrication (MQL) with water in CBN grinding of steel

Abstract: The use of cutting fluids is fundamental to machining processes, mainly when it comes to high heat generation, which is the case of grinding. Thus, lubrication and cooling provided by cutting fluids improve the final quality of the workpiece. However, cutting fluid usage provide some drawbacks concerning environmental, costs and health issues. Therefore, new methods for application and optimization of cutting fluids are being researched aiming to reduce the amount of fluid used, as well as the minimization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 21 publications
(26 reference statements)
0
9
0
2
Order By: Relevance
“…Belentani et al [10] found out that MQL not only improves surface roughness but also helps in disrupting the air barrier formed around the rotating wheel thus lower grinding power obtained. Numerous advantages were found for MQL grinding compared with the conventional technique and dry grinding.…”
Section: Mql Techniques Using Conventional Cutting Fluidmentioning
confidence: 99%
“…Belentani et al [10] found out that MQL not only improves surface roughness but also helps in disrupting the air barrier formed around the rotating wheel thus lower grinding power obtained. Numerous advantages were found for MQL grinding compared with the conventional technique and dry grinding.…”
Section: Mql Techniques Using Conventional Cutting Fluidmentioning
confidence: 99%
“…9 Grinding power average for each tested condition workpiece. According to Belentani et al [8], the main factors that cause the grinding wheel wear are the thermal degradation and the high mechanical stresses in which the grinding wheel is submitted. The temperature control of the process is vital to keep the hardness of the abrasive grains and the bond strength.…”
Section: Diametrical Grinding Wheel Wearmentioning
confidence: 99%
“…Consequently, the workpiece material did not suffer softening by the heat. As the material hardness did not reduce, the grinding wheel is subject to higher stress and the grinding power increased [8]. In short, as the method presents a better cooling effect, the grinding power increased.…”
Section: Grinding Powermentioning
confidence: 99%
See 2 more Smart Citations